Staff Report on the Multilateral Consultation on Global Imbalances with China, the Euro Area, Japan, Saudi Arabia, and the United States. (Policy Papers; Policy Paper, 2007)
Multilateral Consultations are a new tool of multilateral surveillance for the IMF, designed to foster action-oriented debate and policy actions on a problem of systemic or regional importance. The first multilateral consultation focused on facilitating the resolution of global imbalances while sustaining robust global growth. China, the euro area, Japan, Saudi Arabia, and the United States agreed to participate.